(untitled) (Medico Legal Update, 2020)
Background: Vitamin D has different biological actions in the body . Vitamin D has the pleiotropic effects in multiple organ systems, and vitamin D deficiency was suggested to be associated with high blood pressure according to previous reports. Several interventional studies have examined the effect of vitamin D supplementation on high blood pressure patients Objective: To identify Vitamin D level and its correlate with hypertension among old adult in Hilla city – Babylon province.